Complete contracts under incomplete information - Gregorio Curello; Qianjun Lyu; Yimeng Zhang (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We study a moral hazard model in which the output is stochastically determined by both the agent's hidden effort and an uncertain state of the world. We investigate how the contractibility of the ex-post realization of the state affects the principal's incentive to provide information. While detailed information allows the principal to better tailor the effort levels to the revealed states, coarser information enables the principal to base payments on the ex-post realization of states, thereby designing incentive schemes more effectively. Our main result establishes that when the state is contractible, full information is never optimal; however, when the state is not contractible, under certain conditions, full information is optimal.
Keywords: D81; D82; D83; 330; Moral hazard; contractibility; information design; complete contracts; incomplete contracts